Gray Matter Deficits of Cortical-striatal-limbic Circuit in Social Anxiety Disorder - X. Zhang; S. Wang; Q. Gong (European Psychiatry, 2022)
Introduction The extant findings have been of great heterogeneity due to partial volume effects in the investigation of cortical gray matter volume (GMV), high comorbidity with other psychiatric disorders, and concomitant therapy in the neuroimaging studies of social anxiety disorder (SAD).